Intravenous immunoglobulins in patients with COVID-19-associated moderate-to-severe acute respiratory distress syndrome (ICAR): multicentre, double-blind, placebo-controlled, phase 3 trial. Issue 2 (February 2022) - Mazeraud, Aurélien; Jamme, Matthieu; Mancusi, Rossella Letizia; Latroche, Claire; Megarbane, Bruno; Siami, Shidasp; Zarka, Jonathan; Moneger, Guy; Santoli, Francesco; Argaud, Laurent; Chillet, Patrick; Muller, Gregoire; et al.
Summary: Background: Acute respiratory distress syndrome (ARDS) is a major complication of COVID-19 and is associated with high mortality and morbidity. We aimed to assess whether intravenous immunoglobulins (IVIG) could improve outcomes by reducing inflammation-mediated lung injury. Methods: In this multicentre, double-blind, placebo-controlled trial, done at 43 centres in France, we randomly assigned patients (1:1) receiving invasive mechanical ventilation for up to 72 h with PCR confirmed COVID-19 and associated moderate-to-severe ARDS to receive either IVIG (2 g/kg over 4 days) or placebo. Random assignment was done with a web-based system and was stratified according to the participating centre and the duration of invasive mechanical ventilation before inclusion in the trial (<12 h, 12–24 h, and >24–72 h), and treatment was administered within the first 96 h of invasive mechanical ventilation. To minimise the risk of adverse events, the IVIG administration was divided into four perfusions of 0·5 g/kg each administered over at least 8 hours. Patients in the placebo group received an equivalent volume of sodium chloride 0·9% (10 mL/kg) over the same period. The primary outcome was the number of ventilation-free days by day 28, assessed according to the intention-to-treat principle. This trial was registered on ClinicalTrials.gov, NCT04350580 . Findings: Between April 3, and October 20, 2020, 146 patients (43 [29%] women) were eligible for inclusion and randomly assigned: 69 (47%) patients to the IVIG group and 77 (53%) to the placebo group. The intention-to-treat analysis showed no statistical difference in the median number of ventilation-free days at day 28 between the IVIG group (0·0 [IQR 0·0–8·0]) and the placebo group (0·0 [0·0–6·0]; difference estimate 0·0 [0·0–0·0]; p=0·21). Serious adverse events were more frequent in the IVIG group (78 events in 22 [32%] patients) than in the placebo group (47 events in 15 [20%] patients; p=0·089). Interpretation: In patients with COVID-19 who received invasive mechanical ventilation for moderate-to-severe ARDS, IVIG did not improve clinical outcomes at day 28 and tended to be associated with an increased frequency of serious adverse events, although not significant. The effect of IVIGs on earlier disease stages of COVID-19 should be assessed in future trials. Funding: Programme Hospitalier de Recherche Clinique.